Jenis-Jenis Kenakalan Remaja Dan Faktor-Faktor Yang Mempengaruhi Di Desa Merak Rejo Kecamatan Bawen Kabupaten Semarang - Een Een; Umbu Tagela; Sapto Irawan (Jurnal Bimbingan dan Konseling Terapan, 2020)
Adolescence is a transitional period, where the life patterns of adolescents undergo changes, including ways of behaving, associating, ways of thinking and various other patterns of life that characterize adolescents. Things that become a reference are adolescents who are unable to control themselves so that they lose control and fall into deviant behavior. This behavior disorder is known as juvenile delinquency. The objectives of this study were (1) To determine the various types of juvenile delinquency in Merak Rejo Village, Bawen District, Semarang Regency (2) To identify the various factors affecting juvenile delinquency in Merak Rejo Village, Bawen District, Semarang Regency and (3) To see the action conducted by the environment and agencies dealing with juvenile delinquency. The research method used is descriptive qualitative. The results showed that (1) the types of juvenile delinquency that were committed were speeding, recklessness, fighting, skipping school, drinking, leaving without saying goodbye, being noticed, asocial, watching porn and smoking, (2) The factors that influence juvenile delinquency are family conditions, community conditions, peers, social media, TV, lack of religious knowledge and low socioeconomic knowledge and (3) family, village heads, chairman of the neighborhood association, neighborhood chief, community leaders and religious leaders have done preventive measures, repressive measures and rehabilitation measures. The conclusion of this study is the results of the research conducted by the author in accordance with the research objectives. Suggestions from this study are (1) parents to guide and foster their children optimally and (2) agencies at the top to foster families and adolescents.